Correction: Spatially heterogeneous dynamics of cells in a growing tumor spheroid: comparison between theory and experiments. Issue 27 (30th June 2020) - Sinha, Sumit; Malmi-Kakkada, Abdul N.; Li, Xin; Samanta, Himadri S.; Thirumalai, D.
Abstract : Correction for 'Spatially heterogeneous dynamics of cells in a growing tumor spheroid: comparison between theory and experiments' by Sumit Sinha et al., Soft Matter, 2020, 16, 5294–5304, DOI: ; 10.1039/C9SM02277E .